Label‐free detection of fibrillar collagen deposition associated with vascular elements in glioblastoma multiforme by using multiphoton microscopy. (19th September 2016) - JIANG, L.W.; WANG, X.F.; WU, Z.Y.; LIN, P.H.; DU, H.P.; WANG, S.; LI, L.H.; FANG, N.; ZHUO, S.M.; KANG, D.Z.; CHEN, J.X.
Summary: Glioblastoma multiforme (GBM‐WHO grade IV) is the most common and the most aggressive form of brain tumors in adults with the median survival of 10–12 months. The diagnostic detection of extracellular matrix (ECM) component in the tumour microenvironment is of prognostic value. In this paper, the fibrillar collagen deposition associated with vascular elements in GBM were investigated in the fresh specimens and unstained histological slices by using multiphoton microscopy (MPM) based on two‐photon excited fluorescence (TPEF) and second harmonic generation (SHG). Our study revealed the existence of fibrillar collagen deposition in the adventitia of remodelled large blood vessels and in glomeruloid vascular structures in GBM. The degree of fibrillar collagen deposition can be quantitatively evaluated by measuring the adventitial thickness of blood vessels or calculating the ratio of SHG pixel to the whole pixel of glomeruloid vascular structure in MPM images. These results indicated that MPM can not only be employed to perform a retrospective study in unstained histological slices but also has the potential to apply for in vivo brain imaging to understand correlations between malignancy of gliomas and fibrillar collagen deposition.